(untitled) (Law and Safety, 2018)
The work focuses on the study of psychological readiness for change and psychological resilience among employees of the State Criminal-Executive Service of Ukraine. It is shown that in the conditions of reforming, readiness for changes is a psychological condition for successful professional activity and personal self-realization of the staff of the criminal executive service. The content of the concept of “psychological readiness” and “psychological readiness for change” is disclosed, the purposefulness of the study of psychological resilience as one of the factors of psychological readiness for change is substantiated. The purpose of the study was to identify the features of the functioning of psychological readiness for changes in the context of psychological resilience of employees of the State Criminal-Executive Service of Ukraine. The PCRS (Change Personal Readiness Survey) method created by A. Rolnic, S. Heather, M. Gold, C. Hull (translation and adaptation by N. A. Bazhanova and G. L. Bardier) and questionnaire of human resilience (O. O. Rylska) were applied to solve empirical problems. The subjects were employees of the State Criminal-Executive Service of Ukraine, who were divided into groups according to the level of psychological readiness for change. The first group consisted of subjects with a high level of readiness for change, the second – with a low level. The scientific novelty of the research is determined by the fact that, for the first time, the features of psychological resilience in workers of the Criminal Executive Service of Ukraine in the context of psychological readiness for changes were established. It was found that the employees of the Criminal-Executive Service with a high level of psychological readiness for change are distinguished by the greater severity of psychological resilience components, such as adaptation and self-development. It is proved that the groups of employees of the Criminal-Executive Service with different levels of psychological readiness for change show differences in the structure of interrelationships between the components of psychological readiness for change and the components of psychological resilience. In both groups, the growth of psychological resilience on the whole is accompanied by a facilitation of psychological readiness for change. At the same time, in the group with high level of psychological readiness for change, there are almost twice as many interconnections between these phenomena, which indicate a more active interaction between them in this group, in contrast to the low-level group in which this interaction is rather limited. The obtained results allow us to conclude that the subjects with different levels of psychological readiness for change demonstrate differences both in the indicators of psychological resilience and in the structure of interrelations between the components of psychological readiness for change and psychological resilience. Less pronouncedness of a number of components of psychological readiness for change and a certain deficiency of its interaction with psychological resilience can hinder both the successful professional activity of low-level group and their optimal functioning in the personality’s sense. The results obtained in the study can be used to develop programs for psychological support of the professional activities of the staff of the Criminal-Executive Service at the stage of its reformation.